2014
DOI: 10.1002/sia.5410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Co content and heat treatment on mechanical properties of electrolessly deposited Ni‐Co‐P alloys

Abstract: The effects of cobalt content and heat treatment temperature on hardness and wear resistance of nickel-cobalt-phosphorus (Ni-Co-P) are systematically investigated on the electroless alloy deposits composing of cobalt with contents up to 45%. The increase of the cobalt content leads to improved stabilization of grain size and crystallographic structure upon thermal annealing. A moderate annealing temperature of 300°C applied on Ni-45Co-2.6P deposits grants optimum hardness of 959 Hv and relatively low wear loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…, the wear loss of the coating diminishes with Co content, which indicates that cobalt acts as a significant role to enhance the wear resistance. The relationship between wear loss and hardness is well stated by the Archard's law that abrasive wear loss ( V ) is inversely proportional to hardness ( H ) but directly proportional to the normal load ( P ) and sliding distance . In the present measurement, the load and distance remain consistent.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…, the wear loss of the coating diminishes with Co content, which indicates that cobalt acts as a significant role to enhance the wear resistance. The relationship between wear loss and hardness is well stated by the Archard's law that abrasive wear loss ( V ) is inversely proportional to hardness ( H ) but directly proportional to the normal load ( P ) and sliding distance . In the present measurement, the load and distance remain consistent.…”
Section: Resultssupporting
confidence: 77%
“…In the forementioned discussion of XRD patterns, it is found that cobalt can cause refinement of microstructure of the samples, so the micro‐hardness of composite coatings increases with the cobalt content. Another reason proposed here, the improvement of the hardness is probably ascribed to solid solution strengthening mechanism of cobalt element in nickel matrix . Besides, the micro‐hardness of the TiN‐Ni‐Co13‐P coating (414 HV) is higher than that of TiN‐free Ni‐Co‐P coating (391 HV).…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…those that can be deposited individually and those that can be only codeposited. The former group consists of metals that are much nobler than Ni, like Ag [54][55][56][57] and Cu [58][59][60][61][62][63][64][65][66][67][68]; metals that have similar standard potentials, such as Co [69][70][71][72][73][74][75][76] and Sn [77][78][79][80][81][82][83][84][85]; and metals that are more cathodic, like Cr [86,87], Zn [88][89][90][91][92][93][94][95][96][97][98][99][100] and Mn [101]…”
Section: Deposition Of Ni Alloysmentioning
confidence: 99%